2020
DOI: 10.1016/j.toxrep.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic, ethanol, acetaldehyde and noncarcinogenic higher alcohols, esters, and methanol compounds found in traditional alcoholic beverages. A risk assessment approach

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…This is because alcohol affects the immune system and thus increases the risk of developing certain diseases [ 20 ]. Alcohol has long- and short-term effects on every organ in the body, so there is no "safety" limit to consumption [ 21 ]. Moreover, the risk of deteriorating health increases with each glass of alcohol consumed [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because alcohol affects the immune system and thus increases the risk of developing certain diseases [ 20 ]. Alcohol has long- and short-term effects on every organ in the body, so there is no "safety" limit to consumption [ 21 ]. Moreover, the risk of deteriorating health increases with each glass of alcohol consumed [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of ethanol in alcoholic beverages is different and it’s about 4–6% in beer, 7–15% in wine, and 40–95% in distilled beverages [ 9 ]. Furthermore, it is reported that traditional alcoholic beverages have a higher human safety level rather than bulk beverages produced by individuals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the HI is more than 1; the food involved is considered a risk to the concerned consumers. When the HI is less than 1, the food involved is considered as acceptable (no concern) to the concerned consumers [ [31] , [32] , [33] ].…”
Section: Methodsmentioning
confidence: 99%